2023
DOI: 10.1080/09506608.2023.2199617
|View full text |Cite
|
Sign up to set email alerts
|

A review of the processing, microstructure and property relationships in medium Mn steels

Abstract: Medium Mn steels are an emerging class of 3rd generation advanced high-strength steels. These steels have received significant attention due to their high strengths, large ductilities and also lower cost compared to their predecessor high Mn Twinning Induced Plasticity (TWIP) steels. Additionally, medium Mn steels have been found to exhibit TWIP and/or Transformation Induced Plasticity (TRIP) effects which can be harnessed to give a high strain hardening rate. Many thermomechanical processing concepts in the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(4 citation statements)
references
References 206 publications
0
4
0
Order By: Relevance
“…It can be seen that the increase of alloy elements means that the transformation time of proeutectoid ferrite during the cooling process is advanced due to the increase of Ae3 temperature [33,34]. It also means that during the cooling process, the formation of ferrite will happen before it would in steel [35]. Therefore, when the slab enters the straightening machine during continuous casting, the surface temperature due to the effect of reheating should return to above 800 °C.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It can be seen that the increase of alloy elements means that the transformation time of proeutectoid ferrite during the cooling process is advanced due to the increase of Ae3 temperature [33,34]. It also means that during the cooling process, the formation of ferrite will happen before it would in steel [35]. Therefore, when the slab enters the straightening machine during continuous casting, the surface temperature due to the effect of reheating should return to above 800 °C.…”
Section: Discussionmentioning
confidence: 99%
“…It can be seen that the increase of alloy elements means that the transformation time of proeutectoid ferrite during the cooling process is advanced due to the increase of Ae3 temperature [33,34]. It also means that during the cooling process, the formation of ferrite will happen before it would in steel [35]. Therefore, when the slab enters the straightening machine during continuous casting, the surface temperature due to the effect of reheating should return to above 800 • C. The expansion of the two-phase region leads to the extension of the insulation time of the billet in the two-phase region, and proeutectoid ferrite precipitation is also promoted when the grain boundary satisfies certain thermodynamic conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Mechanical twinning, a common phenomenon in many metallic materials, including medium-Mn, facilitates material deformation through the simultaneous cooperative shear of numerous planes, enabling large shear strains. Both TRIP and TWIP significantly increase the work hardening rate and strengthen the material [4,[21][22][23]. Previous studies on medium-Mn indicate that mechanical twinning was observed at an early age of 8% in engineering strains, and it is assumed that austenite did not transform before this strain [6].…”
Section: Introductionmentioning
confidence: 94%
“…As potential candidates in new advanced high-strength steels, medium-Mn steels are particularly attractive for manufacturing energy-absorbing parts of automotive body in white, because they possess an excellent strength-ductility combination and have a low cost. [1,2] Despite these attractive properties, the practical application of this steel grade is hindered by its relatively low yield strength (YS), which is ascribed to the soft matrix after intercritical annealing. [3,4] Considering the high safety standards and weight reduction in the future automotive industry, medium-Mn steels with high YS (>850 MPa) and low density should be designed.…”
Section: Introductionmentioning
confidence: 99%